Improving the methodology of training load and injury risk research: an analysis of analyses - Bache-Mathiesen, L. K. (Norges Idrettshogskole, 2023)
Background: Sport injuries burden professional and recreational athletes. In 2021, Norwegian hospitals operated 1 462 anterior cruciate ligaments, and 62% of these happened during sports activity. To prevent injuries, it may be possible to change the training load. Unfortunately, how training load can be altered to achieve desired outcomes is unknown, because the relationship between training load and injury risk has proven difficult to study. The ability of currently used statistical methods to capture this complex relationship is either limited, or unknown. Consequently, studies have employed a plethora of statistical approaches. Systematic reviews have reported inconsistent and even conflicting findings both within and between studies, and declared the studies too variable to compare in analyses. Experts have questioned the evidence supporting training load as an injury prevention tool, and called for improved statistical methodology. Despite this, few studies have recommended alternatives, and those who have, have not tested the methods` accuracy or precision. The validity of recommended methods is therefore unknown. To improve research on injury prevention programs, knowledge is needed on how to statistically determine the relationship of training load and injury risk.